Indonesia Public Transportations: A Mapping What Needs to be Improved - Saraswati, Trisha Gilang; Batara, Jagat (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of this study is to demonstrate the potential of Importance of Performance Analysis as a decision-making tool to assess the performance of Indonesia public transportation in delivering quality services.Design/methodology/approach: Data were collected through questionnaire where the respondents were asked to provide importance and performance scores about Indonesia public transportation based on SERVQUAL model. In order to qualify the sample, individuals have used public transportation at least 1 time within the previous three months. The gap analysis and importance performance analysis maps were employed to analyze the dataFindings: 22 SERVQUAL indicators are mapped into the importance performance analysis diagram consisting of the concentrate here quadrant, keep up the good work quadrant, low priority quadrant and possible overkill quadrant where the quadrants show the level of performance and importance of every indicators.Research limitations/implications: This study is focus on public transportation in Indonesia. Further research could focus on public transportation in other cities or countries.Practical implications: A practical implication of the mentioned findings is that the mapping can be a decision- making tool for the government identifying and improve public transportation quality services.Originality/value: Public transportation can use this approach to improve their service management by employed the result mapping.